Rituales de género para el orden cósmico : luchas chamánicas mapuche por la totalidad - Bacigalupo, Ana Mariella (Universidad de Chile, 2003)
The struggle for uholeness-the melding of all experiencie and knowledge of the world-is central to the parctice of machi, or Mapuche shamans, in southern Chile. I explore how the gender and generational aspects of Mapuche persons are extender to the socio-cosmological order, to Mapuche ritual practice, and to the creation of a holistic machi personhood. I outline the application of holistic personbood in Mapuche cosmology and the analyze its performance in three kinds of Mapuche rituals. First, in divination rituals, gender difference is enacted by machi and dungumachife ("ritual interpreter for machi"), and wholeness is expressed though their ritual partnership. I demostrate that ecstatic and formal discourses are gendered independently of the sex of the actors. Second, in community-wide ngillatun rituals, difference is impersonated by diverse actors, and wholeness is enacted collectively to integrate the ritual community. I demostrate that both sex-based and performative dimensions of gender and generation are crucial for collective renditions of wholeness. Third, in individual healing rituals, difference is subsumed by the machi, who enacts wholeness as wellness, and the performative dimension of gender prevails over the notion of gender as linked to sex. Machi, both male and female, assume masculine, feminine, and cogendered identities-moving berween masculine and feminine, and cogendered identities-moving between masculine and feminine gender polarities or combining them-for the purpose of bealing. I conclude by analyzing the implications of ritual wholeness for theories of gender and embodiment and for Mapuche identity politics.